PENGARUH TELEREHABILITASI SELF CARE OREM TERHADAP MOBILISASI PASIEN PASCA STROKE: The Effect of Orem’s Self Care Telerehabilitation on Mobilization of Post Stroke Patients - Mohammad Fahrul Arifin; Heri Kristianto; Loeki Enggar Fitri; Ahmad Fauziansyah; Arifin, Mohammad Fahrul Arifin (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Post-stroke patients need to receive telerehabilitation to increase mobility, telerehabilitation approaches Orem's Self Care Theory to increase mobility so that recurrent strokes will be greatly minimized. The research method for this research is Quasi Experimental with a pre-post test design approach and purposive sampling technique. The population is post-stroke patients in the Neurology Polyclinic and Orchid Room at RSUD Dr. R Koesma Tuban numbered 50 patients. 25 people in the control group were given education and 25 people in the intervention group were given a rehabilitation video. The chi square test and normality test were carried out and data analysis used the Mann Whitney test. Mobilization during the pre test with the average score in the control group was 23.72 and the intervention group was 27.28. The Std value. Deviation 10.016 with p value = 0.381. Mobilization during the post test with the average score in the control group was 31.8 and the intervention group was 19.2. The Std value. Deviation 16.427 with p value = 0.002. Based on the results of this study, it was found that there was a significant increase in mobilization scores after being given telerehabilitation in the intervention group. Keywords: Mobilization; Orem's Self Care; Telerehabilitation